User Interface Design Aplikasi Mobile Hola-Hola - Muhammad Divo Yursal; Dwi Mutia Sari (Lembaga Pengembangan Kinerja Dosen, 2023)
The background for the design of the user interface for the Hola-Hola mobile application is the problems that exist in the Hola-Hola premium gadget accessories business. Namely the limited space for product sales in businesses, which only provide offline services, so marketing is not effective and results in product sales being relatively low. This design uses the